A multinational study on motor function in early-onset FSHD. (10th April 2018) - Mah, Jean K.; Feng, Jia; Jacobs, Marni B.; Duong, Tina; Carroll, Kate; de Valle, Katy; Carty, Cara L.; Morgenroth, Lauren P.; Guglieri, Michela; Ryan, Monique M.; Clemens, Paula R.; Thangarajh, Mathula; et al.
Abstract : Objectives: To investigate motor function associations with age, sex, and D4Z4 repeats among participants with early-onset facioscapulohumeral muscular dystrophy (FSHD) type 1 as defined by weakness onset before 10 years of age. Methods: We collected standardized motor assessments, including manual muscle testing (MMT), quantitative muscle testing, functional motor evaluations, and clinical severity scores (CSSs), at 12 Cooperative International Neuromuscular Research Group centers. To measure associations, we used linear regression models adjusted for sex, evaluation age, age at onset of weakness, and D4Z4 repeats. Results: Among 52 participants (60% female, mean age 22.9 ± 14.7 years), weakness was most pronounced in the shoulder and abdominal musculature. Older enrollment age was associated with greater CSSs ( p = 0.003). When adjusted for enrollment age, sex, and D4Z4 repeats, younger age at onset of facial weakness was associated with greater CSSs, slower velocities in timed function tests, and lower MMT scores ( p < 0.05). Conclusion: Significant clinical variability was observed in early-onset FSHD. Earlier age at onset of facial weakness was associated with greater disease severity. Longitudinal assessments are needed to determine the rate of disease progression in this population.